Reading the Youtube sitcom My best gay friends: what it means to be gay in Vietnam. Issue 5 (3rd September 2019) - Nguyen, Thi Huyen Linh
ABSTRACT: My Best Gay Friends is a Vietnamese gay sitcom web-series that was well received by Youtube viewers. It is very rare to find non-stigmatised representations of homosexual people in Vietnamese mainstream media, especially as main characters. This series was created by a group of gay, lesbian and transgender (GLT) people and was circulated through the online platform Youtube. The growth of the Internet as an alternative channel for creating and distributing media has led to the increasing visibility of homosexual people. The interactive nature of Youtube, which allows audiences to comment on each video, has left room for active engagement with, consumption of and production of media content. In this article I explore how Youtube as an alternative media platform is used to negotiate and construct ideas about subjectivity and sexualities. I read the representation of gay characters in the sitcom in the context of legal, societal and cultural discourses on LGBT issues in contemporary Vietnam. The textual analysis of the series and its comments will shed light on how homosexual visibility has been shaped by Vietnamese heteronormative culture, but also how heteronormativity has been challenged.